Defective Mammary Epithelial Outgrowth in Transgenic EKAREV-NLS Mice: Correction via Estrogen Supplementation and Genetic Background Modification - Brezak, Matea; Sumbalova Koledova, Zuzana (Journal of mammary gland biology and neoplasia, 2025)
Fluorescent biosensors offer a powerful tool for tracking and quantifying protein activity in living systems with high temporospatial resolution. However, the expression of genetically encoded fluorescent proteins can interfere with endogenous signaling pathways, potentially leading to developmental and physiological abnormalities. The EKAREV-NLS mouse model, which carries a FRET-based biosensor for monitoring extracellular signal-regulated kinase (ERK) activity, has been widely utilized both in vivo and in vitro across various cell types and organs. In this study, we report a significant defect in mammary epithelial development in EKAREV-NLS C57BL/6J female mice. Our findings reveal that these mice exhibit severely impaired mammary epithelial outgrowth, linked to systemic defects including disrupted estrous cycling, impaired ovarian follicle maturation, anovulation, and reduced reproductive fitness. Notably, estrogen supplementation was sufficient to enhance mammary epithelial growth in the EKAREV-NLS C57BL/6J females. Furthermore, outcrossing to the ICR genetic background fully restored normal mammary epithelial outgrowth, indicating that the observed phenotype is dependent on genetic background. We also confirmed the functional performance of the biosensor in hormone-supplemented and outcrossed tissues through time-lapse imaging of primary mammary epithelial cells. Our results underscore the critical need for thorough characterization of biosensor-carrying models before their application in specific research contexts. Additionally, this work highlights the influence of hormonal and genetic factors on mammary gland development and emphasizes the importance of careful consideration when selecting biosensor strains for mammary studies.
Keywords: Mice, Transgenic; Biosensor; epitelové buňky; Mammary epithelium; Estradiol supplementation; myši transgenní; Mammary Glands, Animal; Mice; zvířata; Genetic background; Biosensing Techniques; Estrogens; Genetic Background; estrogeny; ERK signaling; Hormonal imbalance; EKAREV–NLS mouse; biosenzitivní techniky; Epithelial Cells; ženské pohlaví; myši; mléčné žlázy zvířat; Animals; Mice, Inbred C57BL; genetické pozadí; myši inbrední C57BL; Female